Characterization and evaluation of drumstick (Moringa oleifera Lam.) accessions for yield and quality - Anitta Judy Kurian (Department of Vegetable Science, College of Horticulture, 2019)
Drumstick (Moringa oleifera Lam.), belonging to the family Moringaceae is one of the most useful tree with a variety of potential uses. Large variability exists in drumstick since the crop is cross pollinated and naturalized in many areas. The study entitled “Characterization and evaluation of drumstick (Moringa oleifera Lam.) accessions for yield and quality’’ was conducted during January to December 2018. Twenty five accessions were catalogued based on IPGRI minimal descriptors (2013). Data on morphological, quantitative and biochemical characters were recorded for one calendar year (2018) for further analysis. Tree shape varied from upright to spreading. Grey coloured barks were recorded in majority of accessions except in VKMo 3, VKMo 4 and VKMo 8 which had white bark colour. All accessions produced pale green coloured young shoots with purple tinge. Foliage density at flowering period varied from sparse, medium to dense. Leaflet shape varied from ovate, oblong to elliptical and leaf apex from obtuse to acute. Both secondary and tertiary flowering branchlets were observed. Flowers produced in all the accessions had triangular shaped, polysepalous nature, pale green coloured calyx; corolla having triangular shape, polypetalous nature and cream colour. Fresh fruit pulp colour was white in all accessions. Taste of fresh fruit pulp was palatable in all flowering types except VKMo 3, VKMo 6, VKMo 11, VKMo 13 and VKMo 29, which were bitter in taste. Out of twenty five accessions, three were leafy types viz. VKMo 32, VKMo 35 and VKMo 38. Two peaks of flowering viz. January- April and September- November were observed in VKMo 2, VKMo 7, VKMo 12, VKMo 15, VKMo 16 and VKMo 17. Accession VKMo 3 recorded highest tree height (7.68 m) and trunk girth (65.8 cm). Accession VKMo 10 recorded highest fruit length (89.50 cm), fruit girth (6.72 cm) and number of ridges/fruit (10.50). Highest fruit weight was recorded in VKMo 9 (160.00 g). Accession VKMo 6 recorded highest number of seeds per fruit (21.20). Highest number of fruits/tree was recorded in VKMo 2 (22.21) and total fruit yield/tree in VKMo 3 (1775.54 g/tree). Estimation of